2014
DOI: 10.1186/1472-6920-14-58
|View full text |Cite
|
Sign up to set email alerts
|

The temporal decline of idealism in two cohorts of medical students at one institution

Abstract: BackgroundA number of studies have indicated that students lose idealistic motivations over the course of medical education, with some identifying the initiation of this decline as occurring as early as the second year of the traditional US curricula. This study builds on prior work testing the hypothesis that a decline in medical student idealism is detectable in the first two years of medical school.MethodsThe original study sought to identify differences in survey responses between first-year (MS1) and seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 24 publications
(32 reference statements)
0
27
2
2
Order By: Relevance
“…As students enter medical college around the age of 17–18 years, the preclinical year is of prime importance as a time for their first exposure to a professional learning environment. While the student entering medical school may not yet possess full‐fledged professional values, studies have shown that it is these very students who are the most idealistic with regards to learning key medical skills and fulfilling obligations to their community, attitudes which wane with years of training (Baingana et al, ; Morley et al, ; Pagnin et al, ; Mader et al, ), and they are less self‐centered than their senior counterparts (Klemenc‐Ketis and Vrecko, ). The first year of medicine would be an ideal foundation to begin the integration of professionalism teaching into medical education in India.…”
Section: Introductionmentioning
confidence: 99%
“…As students enter medical college around the age of 17–18 years, the preclinical year is of prime importance as a time for their first exposure to a professional learning environment. While the student entering medical school may not yet possess full‐fledged professional values, studies have shown that it is these very students who are the most idealistic with regards to learning key medical skills and fulfilling obligations to their community, attitudes which wane with years of training (Baingana et al, ; Morley et al, ; Pagnin et al, ; Mader et al, ), and they are less self‐centered than their senior counterparts (Klemenc‐Ketis and Vrecko, ). The first year of medicine would be an ideal foundation to begin the integration of professionalism teaching into medical education in India.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study suggested that students’ loss of idealism begins early in their training . We now train facilitators to discuss the HC across all years of the programme.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggested that students' loss of idealism begins early in their training. 5 We now train facilitators to discuss the HC across all years of the programme. Helping faculty members to appreciate the impact of their own behaviours on students may improve the informal learning environment for students, and we now run training sessions for faculty members, naming and exploring the HC and discussing its potential impact on student development.…”
Section: Questioning and Critiquing Role Modelsmentioning
confidence: 99%
See 2 more Smart Citations